The role of monocytes in thrombotic diseases: a review - Han, Zhongyu; Liu, Qiong; Li, Hongpeng; Zhang, Meiqi; You, Luling; Lin, Yumeng; Wang, Ke; Gou, Qiaoyin; Wang, Zhanzhan; Zhou, Shuwei; Cai, YiJin; Yuan, Lan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular and cerebrovascular diseases are the number one killer threatening people's life and health, among which cardiovascular thrombotic events are the most common. As the cause of particularly serious cardiovascular events, thrombosis can trigger fatal crises such as acute coronary syndrome (myocardial infarction and unstable angina), cerebral infarction and so on. Circulating monocytes are an important part of innate immunity. Their main physiological functions are phagocytosis, removal of injured and senescent cells and their debris, and development into macrophages and dendritic cells. At the same time, they also participate in the pathophysiological processes of pro-coagulation and anticoagulation. According to recent studies, monocytes have been found to play a significant role in thrombosis and thrombotic diseases of the immune system. In this manuscript, we review the relationship between monocyte subsets and cardiovascular thrombotic events and analyze the role of monocytes in arterial thrombosis and their involvement in intravenous thrombolysis. Finally, we summarize the mechanism and therapeutic regimen of monocyte and thrombosis in hypertension, antiphospholipid syndrome, atherosclerosis, rheumatic heart disease, lower extremity deep venous thrombosis, and diabetic nephropathy.